Generalized Reduced Gradient Optimization for Ammunition caliber 57 mm C-60 Het - Muhammad Sjahid Akbar (Jurnal ILMU DASAR, 2009)
Ammunition is a tool that works to sabotage or destroy the target. Weapons Laboratory in TNI AL have ammunition caliber 57 mm C-60 Het, with more than 10 years of age. Ammunition caliber 57 mm C-60 Het has three sections, projectile, propellant, and primer.  Primary part of this ammunition is not working well, so that it is necessary to repair this section. Repairing of primary part is done  by changing the chemical compound AB3, DF3, and GI2. The purpose of this study is to determine chemical composition of primary part, so that it can optimize the sensitivity and detonation. The results show that the optimization begins with model estimation of two response by Ordinary Least Square (OLS). Futher, model estimation for each response is tranformed into individual desirability function to form joint desirability function. Results optimization caliber ammunition 57 mm C-60 by Generalized Reduced Gradient method (GRG), obtained sensitivity of 9.93 cm and the detonation of 108.68 dB, with compotition AB3 compound was 48.8 grams, DF3 compound was 21.0025 grams, and GI2 compound was 17 grams.